Đặt A=(n+3)(n+12)
Ta xét các trường hợp sau:
TH1: n\(⋮\)2
=>(n+12)\(⋮\)2
=>A\(⋮\)2
TH2: n\(\equiv\)1(mod 2)
=>(n+3)\(⋮\)2
=>A\(⋮\)2
Do đó \(\forall n\in\)N thì A\(⋮\)2(đpcm)
Với \(n=2k\Rightarrow n+12=2k+12⋮2\)
\(\Rightarrow n+12⋮2\)
\(\Rightarrow\left(n+3\right)\left(n+12\right)⋮2\)
Với \(n=2k+1\Rightarrow n+3=2k+1+3=2k+4⋮2\)
\(\Rightarrow n+3⋮2\)
\(\Rightarrow\left(n+3\right)\left(n+12\right)⋮2\)
Vậy với mọi số tự nhiên n thì tích (n+3)(n+12) là số chia hết cho 2.
( n + 3 ) ( n + 12 )
+) Xét n là số lẻ
=> ( n + 3 ) là số chẵn => ( n + 3 ) ( n + 12 ) chia hết cho 2
+) Xét n là số chẵn
=> ( n + 12 ) là số chẵn => ( n + 3 ) ( n + 12 ) chia hết cho 2
+) Xét n = 0
=> ( n + 12 ) = 12 => ( n + 3 ) ( n + 12 ) chia hết cho 2